Hypoalbuminemia and cisplatin-induced acute kidney injury - Yin, Wen-Jun; Huang, Yu-Jie; Zhu, Qing; Lin, Xiao-Qing; Piao, Hui-Ling; Yu, Qian-Qian; Lai, Chang-Hong; Zhou, Guang-Liang; Zhou, Ling-Yun; Liu, Kun; Zuo, Xiao-Cong; Zuo, Shan-Ru (Frontiers in Pharmacology, 2024)
Background: Cisplatin binds to serum albumin in the body at a rate of 90%, and high levels of free cisplatin are a significant cause of its nephrotoxicity. Therefore, hypoalbuminemia theoretically poses a significant risk factor for cisplatin-induced acute kidney injury (CIA) and can be easily corrected. However, existing research results are inconsistent. Our aim is to confirm the association between hypoalbuminemia and CIA through a meta-analysis and a dual-center real-world data study. Methods: First, we used a random-effects meta-analysis to summarize the odds ratio (OR) of the risk relationship between hypoalbuminemia and CIA. Then, we conducted a retrospective analysis of patients using cisplatin from Xiangya Third Hospital of Central South University (2014-2023) and Hunan Cancer Hospital (2019-2023) to analyze the relationship between hypoalbuminemia and CIA. Results: The meta-analysis, which included six studies involving 4,359 cases, showed that hypoalbuminemia is associated with an increased risk of CIA (OR, 2.13; 95% CI,. A total of 5,452 and 25,214 patients from Xiangya Third Hospital and Hunan Cancer Hospital, respectively, were included. Both centers found a significant association between hypoalbuminemia and an increased risk of CIA (OR, 2.76; 95% CI, 1. OR, 3.76; 95% CI,, and the sensitivity analysis results were consistent. Conclusion: Through meta-analysis and dual-center realworld data studies, we confirmed that hypoalbuminemia is an independent risk factor for CIA. Therefore, it is recommended that patients using cisplatin undergo serum albumin level testing and regular monitoring during treatment. Actively adjusting albumin levels may reduce the risk of CIA.